2014
DOI: 10.1002/nla.1937
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping for preconditioners based on incomplete factorizations and nested arrow form

Abstract: International audienceIn this paper, we discuss the usage of overlapping techniques for improving the convergence of preconditioners based on incomplete factorizations. To enable parallelism, these preconditioners are usually applied after the input matrix is permuted into a nested arrow form using k-way nested dissection. This graph partitioning technique uses k-way partitionning by vertex separator to recursively partition the graph of the input matrix into k subgraphs using a subset of its vertices called a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…We display a simple example from [20] to describe shortly how the overlapping procedure works in practice. We consider a 5 × 5 matrix having the structure shown in Figure 2(a).…”
Section: Examplementioning
confidence: 99%
See 2 more Smart Citations
“…We display a simple example from [20] to describe shortly how the overlapping procedure works in practice. We consider a 5 × 5 matrix having the structure shown in Figure 2(a).…”
Section: Examplementioning
confidence: 99%
“…From Eqn. (20), we can construct the edges fromΩ 1 toS. These are the nonzero entries of the overlapped interface blockF 1 , adopting the same notation as in (6).…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a preconditioner with a very cheap construction cost, since it requires only the factorization of diagonal blocks. In our recent work [13], we have shown that by using overlapping techniques similar to the ones from domain decomposition methods, the convergence of NSSOR is greatly improved. Without going further into the details of the overlapping techniques, we note that the experiments from section 4 present the convergence of NSSOR with overlapping, in which the variables at the interface between the different subdomains are duplicated.…”
Section: Definition 1 Letmentioning
confidence: 99%
“…The number of innermost diagonal blocks that can be computed in parallel corresponds to P , the number of processors used in the parallel computation, however the recursion depth is only two. While NFF remains an efficient preconditioner with this new reordering, the other preconditioners presented in [10] require the usage of overlapping techniques as explained in [13].…”
Section: Introductionmentioning
confidence: 99%